Non-state actors as quasi-subjects of transnational organised crime: implications for the security of states - Меrkushin, Vladimir V. (Journal of the Belarusian State University. International Relations, 2022)
We discuss the legal status of non-state actors in the context of the global fight against transnational organised crime and the security of states. We address the topic from the perspectives of international law (including criminal law), international security and human rights. We conclude that non-state actors such as multinational corporations, private military and security companies, and non-governmental organisations may become quasi-actors of transnational organised crime. Contributing to this probability are their uncertain legal status under international law, certain corporate practices and attitudes, obscure financial flows, and vulnerability of international and national public authorities to corrupt practices, among others.
Keywords: non-state actors; transnational organised crime; state security; strengthening the security of states; multinational corporations; private military and security companies; non-governmental organisations